A conversation with a stranger: Debunking religiosity and poverty in South Africa - Mpofu, Buhle (HTS teologiese studies, 2021)
My previous research explored narratives and discourses from marginalised migrants in their quest for survival. This contribution approached the South African context through the lens of the UN Sustainable Development Goal (SDG) 1 ‘Ending poverty in all its forms’ and employed John Hick’s notion of ‘soul-making’ to analyse themes that emerged from a summary of a conversation with a stranger. Faith in God, forgiveness and vulnerability are thematically discussed within the context of the struggle for survival through a conversation held with a homeless man in Sinoville, Pretoria, on 03 August 2021. Inspired by this conversation, the article highlights religious expressions of the homeless, their vulnerability and their perceptions of God to contend that some of the homeless prayerfully deploy religiosity and seek God’s guidance to practise Christian values in their daily lives to survive on the margins of society. The contribution challenges dominant narratives on poverty in the context of homelessness and religiosity. The contribution concludes that current developmental discourses need to be decolonised to promote new models for ‘development from below’ which appreciate the role of religion and promote participation of the marginalised in local development initiatives.Contribution: This research contributed to the UN SDG 1 on ending poverty in all its forms by interrogating the vulnerability and religious narratives of homeless people in South Africa through the story of an encounter with a homeless stranger.